Four illustrators William Brunton, Paul Gray, Mathew Lawless, William McConnell - Bailey, Christopher M. C. (Trinity College (Dublin, Ireland). Department of History of Art and Architecture, 1983)
Excerpt from introduction: Between 1855 and 1870 the standard of the art of illustrated magazines in England rose to a new height. There was no single reason for this, it was the result of social, economic, legislative, technical and artistic changes and developments. The relatively stable economic and political climate of mid-Victorian Britain gave the average citizen more leisure time than ever before, and literature, of all varieties, played no small part in filling it. While entertainment was the prime motivation behind such reading, many, but particularly those of the rising middle classes, saw it playing an important social function as well. This function was to herald and strengthen the virtues of moral and intellectual improvement. While newspapers, illustrated weeklies and specialized journals were informative, the majority of ’improving’ literature was of a religious nature. In 1864 the total yearly circulation of London-published weeklies (excluding newspapers) stood at 2,404,000, of which approximately one third were predominantly religious and/or educational. Of the 2,490,000 monthlies circulated in the same year nearly two million were, in one form or another religious …
Access restricted on volume 2 due to image copyright concerns. Please consult print copy in the Library.
Keywords: History of Art and Architecture, M.Litt.; M.Litt. Trinity College Dublin